2019
DOI: 10.1136/tsaco-2018-000203
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of intramedullary nailing of femoral shaft fractures with third fragments: a retrospective analysis of risk factors for delayed union

Abstract: BackgroundThis study retrospectively evaluated the clinical outcomes of intramedullary nailing of femoral shaft fractures with third fragments and analyzed the risk factors for delayed union.MethodsRetrospective analyses involving 51 patients who underwent intramedullary nailing of femoral shaft fractures with third fragments (AO classification type B, 35 cases; type C, 16 cases) were conducted. Delayed union was defined as either more than 10 months required for callus formation in more than three of the four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
23
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 26 publications
3
23
1
Order By: Relevance
“…The most important finding of the present study was that IC significantly increased the nonunion rate in simple femoral shaft fractures at 12 and 24 months after surgery. Studies have demonstrated that a greater fracture severity was associated with a higher nonunion rate [ 19 , 20 ]. Noumi et al conducted a retrospective analysis involving 89 femoral shaft open fractures treated with IMN [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most important finding of the present study was that IC significantly increased the nonunion rate in simple femoral shaft fractures at 12 and 24 months after surgery. Studies have demonstrated that a greater fracture severity was associated with a higher nonunion rate [ 19 , 20 ]. Noumi et al conducted a retrospective analysis involving 89 femoral shaft open fractures treated with IMN [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, we felt the treatment of the femoral fracture was insufficient as there was a critical defect of the lateral cortex of the femur that was disregarded. In fact, several studies highlight the importance that the presence of a third fragment in femoral shaft fractures may have in the development of non-union [ 10 ]. Secondly, the patient was still symptomatic in regard to his iliac wing fracture.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, closed reduction is said to preserve the soft tissue integrity and blood supply, leading to satisfactory prognoses [2,[18][19][20]. However, several studies have shown that open reduction has similar to superior outcomes [6, [21][22][23]. In our study, the open reduction group had a shorter time to union (7.39 vs. 9.18 months, p = 0.025) and signi cantly better strength of union in the early postoperative stage.…”
Section: Discussionmentioning
confidence: 99%
“…The vascular supply to the reversed fragments may be strangulated and become compromised in the setting of an altered morphology [6]. Hamahashi et al concluded that among the risk factors of delayed union, displacement is the only risk factor that could be modi ed with intraoperative reduction [21]. Achieving a quality reduction, eliminating the third-fragment effect, and facilitating bone union are more likely with the open reduction technique than with closed reduction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation